2013
DOI: 10.1371/journal.pone.0068602
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HSP90 as Potential Biomarker of Biliary Atresia Using Two-Dimensional Electrophoresis and Mass Spectrometry

Abstract: Biliary atresia (BA) is a devastating cholestatic liver disease targeting infants. Current diagnosis depends on surgical exploration of the biliary tree. The aim of the present study was to identify potential biomarkers for the diagnosis of biliary atresia (BA). Two-dimensional electrophoresis was utilized for the identification of proteins that were differentially expressed in liver biopsies of 20 BA patients and 12 infants with non-BA neonatal cholestasis (NC) as controls. Using mass spectrometry, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Mass spectrometry experiments to identify differentially expressed proteins in 20 BA liver biopsies compared to 12 non-BA, neonatal cholestasis livers found that heat shock protein 90 (HSP90) was significantly down-regulated in BA livers, and was the most significantly altered protein. This suggests that HSP90 could serve as a potential biomarker for BA 48 . We therefore hypothesized that a gene-environment interaction may explain isolated BA where a predisposing genetic factor exists and an external insult triggers the initiation of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…Mass spectrometry experiments to identify differentially expressed proteins in 20 BA liver biopsies compared to 12 non-BA, neonatal cholestasis livers found that heat shock protein 90 (HSP90) was significantly down-regulated in BA livers, and was the most significantly altered protein. This suggests that HSP90 could serve as a potential biomarker for BA 48 . We therefore hypothesized that a gene-environment interaction may explain isolated BA where a predisposing genetic factor exists and an external insult triggers the initiation of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…Transcriptome analyses revealed that genes involved in protein folding were up-regulated at M2 when the most dramatic metamorphic events occurred. Hsp90 was identified as a candidate key factor during liver metamorphosis because of its involvement in protein folding [ 31 ], metamorphosis in invertebrates [ 15 , 18 ], and human biliary atresia [ 32 ]. Increased hsp90 mRNA expression coincided with the onset (M1), gall bladder disappearance (M3), and final stages (M6-M7) of metamorphosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that HSP90 blocker geldanamycin facilitated and hsp90 siRNA treatment synchronized gall bladder degeneration during liver metamorphosis in the sea lamprey. Coincidentally, proteomic analyses comparing BA and non-BA neonatal cholestasis patients showed that HSP90 was the most significant biomarker that was down-regulated in BA patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…STIP1 is a chaperone that assists in the transfer of proteins from HSP70 to HSP90, which are an integral part of the heat shock response pathway. Mass spectrometry experiments to identify differentially expressed proteins in 20 BA liver biopsies compared to 12 non-BA, neonatal cholestasis livers found that HSP90 was significantly down-regulated in BA livers, and was the most significantly altered protein 50 . REV1 encodes a protein similar to the S. cerevisiae mutagenesis protein Rev1 and is known to be involved in DNA repair.…”
Section: Discussionmentioning
confidence: 99%